2011
DOI: 10.1007/s00795-010-0499-y
|View full text |Cite
|
Sign up to set email alerts
|

Plectin deficiency on cytoskeletal disorganization and transformation of human liver cells in vitro

Abstract: Plectin is a versatile cytoplasmic cross-linking protein that connects intermediate filaments to microfilaments, microtubules, and membrane adhesion sites. The cross-linking functions of plectin help organize the cytoskeleton into a stable meshwork important for maintaining uniformity in cell size and shape. As cells of hepatocellular carcinoma are morphologically different from normal human hepatocytes, we hypothesized that altered plectin expression and cytoskeletal organization underlies this pleomorphic tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…FAM83H-FLAG immunoprecipitates contained plectin (supplementary material Table S1), and plectin knockdown, as well as the inhibition of FAM83H and CK-1a, caused keratin filament bundling in HCT116 cells (supplementary material Fig. S3) and a human liver cell line (Liu et al, 2011). Our next task will be proteomic analysis to identify the CK-1a substrates responsible for the rearrangement of keratin filaments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FAM83H-FLAG immunoprecipitates contained plectin (supplementary material Table S1), and plectin knockdown, as well as the inhibition of FAM83H and CK-1a, caused keratin filament bundling in HCT116 cells (supplementary material Fig. S3) and a human liver cell line (Liu et al, 2011). Our next task will be proteomic analysis to identify the CK-1a substrates responsible for the rearrangement of keratin filaments.…”
Section: Discussionmentioning
confidence: 99%
“…The plakin family proteins, which are linker proteins between keratin filaments and various cytoskeletal structures (Wiche, 1998), are major modulators of keratin filament bundling (Boczonadi et al, 2007;Liu et al, 2011;Long et al, 2006;Osmanagic-Myers et al, 2006); however, our knowledge about crucial modulators of keratin filament bundling remains very limited. To further understand the mechanism governing the rearrangement of keratin filaments, identification of novel keratin-associated proteins and kinases responsible for the mechanism is required.…”
Section: Introductionmentioning
confidence: 99%
“…The cross-linking functions of plectin help organize the cytoskeleton into a stable meshwork that is important for maintaining uniformity of cell size and shape. In one study (30), expression of CK18 was shown to be downregulated by suppression of plectin protein, and cytokeratin networks (12,14,(22)(23)(24) and of ERK1/2 in the ERK MAPK pathway (28,29), and regulation of CK18 by Wnt is involved in Akt activation (26,27). Questions regarding the PI3K/Akt and Wnt pathways, and whether CK18 functions as the regulator in these three pathways require further investigation.…”
Section: Interactions With Related Proteinsmentioning
confidence: 99%
“…Therefore, it is assumed that tongue epithelial cells have a "thin" cell structure and that the cytoskeleton is maintained by an intercellular component. Plectin-1 knock down in human liver cells treated with plectin-1 siRNA was shown to induce a decrease in the expression of CK18, the disorganization of intermediate filaments, and an increase in actin fibers [18]. Accordingly, chief cytoskeleton components in human tongue epithelial cells could be other molecules such as actin, tubulin, and heat shock proteins [19].…”
Section: Discussionmentioning
confidence: 99%